إسهامات محمد بن نقيب العطاس في أسلمة المعرفة في العالم الإسلامي المعاصر: The Contributions of Muhammad Naqib Al-Attas in the Islamization of the Contemporary Islamic World - Zhangzhiming; Rahmah Binti Ahmad H. Osman; Muhammad Farhan Rizaludin; Mahaixiang (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص في العصر الحديث، وفي مواجهة الالتزام بالتقاليد والتنمية، كان التعليم الإسلامي دائمًا في حالة اختلال ومعضلة: يعتقد أولئك الذين يلتزمون بالتقاليد أن العلوم خارج الكتب الدينية غير العلوم الدينية بل يعتبرونها من العلوم الدنيوية، ولا يستحق أو لا يمكن تقديره. ونتيجة لذلك، فإن نظام التعليم التقليدي غير قادر على تنمية الأكفاء المناسب للتنمية الاجتماعية؛ بينما يتبع التعليم العلماني نموذج التعليم الغربي، الذي يؤكد فقط على تلقين وتدريس التخصصات التطبيقية، ويتجاهل تعليم القيم --الأمر الذي يؤدي إلى تطوير المادة والثقافة الاجتماعية، وتدهور الحضارة، وتدهور الأخلاق، ويزداد معدل الجريمة، وغيرها من الأمراض الاجتماعية الحديثة. Abstract In the modern era, in the face of adherence to tradition and development, Islamic education has always been in a state of imbalance and dilemma: those who adhere to tradition believe that sciences outside religious books are not religious sciences but rather secular sciences, unworthy or unappreciated. As a result, the traditional education system is unable to cultivate talents suitable for social development; Whereas secular education follows the Western education model, which emphasizes only the indoctrination and teaching of applied disciplines, and ignores values education—leading to the development of social material and culture, the decline of civilization, the decline of morals, an increase in crime, and other modern social ills.